Egyptian Art - Jaromir Malek (UK Phaidon Press, 1999)
"In this introduction, Jaromir Malek, an internationally respected authority, deftly traces Egyptian art from its prehistoric origins through 3000 years of astonishing achievements in the era of the pharaohs to the conquest of Egypt by the Romans. He outlines artistic trends in each period, linking them to economic, political and spiritual developments, and discusses the full range of artistic output: monumental architecture, sculpture, wall-reliefs and paintings, furniture, jewellery, papyri and pottery. He concludes with a fascinating account of Egypt's influence on modern art. Illustrations document the immense variety and superb quality of the art and architecture of one of the world's great civilizations."--BOOK JACKET.
Riches of the black land: conditions for success -- The quest for form: predynastic and early dynastic periods -- Pointing to the stars: the Old Kingdom -- Upheaval and stability: the Middle Kingdom, rise and fall -- An art of opulence: the New Kingdom, early stages -- Heretic city: the Amarna Period and its aftermath -- Colossal obsession: the Ramessides and their successors -- Last brilliance: the late period -- Outside intervention: the Ptolemaic and Roman periods -- Wonderful things: Egypt's continuing presence.
Cover title
Keywords: Art, Egyptian; Art, Ancient -- Egypt; General; Ancient Egypt; Archaeology